Clinical and Neuroimaging Correlation in Patients with COVID-19 - Yoon, B.C.; Buch, K.; Lang, M.; Applewhite, B.P.; Li, M.D.; Mehan, W.A.; Leslie-Mazwi, T.M.; Rincon, S.P. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Coronavirus disease 2019 (COVID-19) is increasingly being recognized for its multiorgan involvement, including various neurological manifestations. We examined the frequency of acute intracranial abnormalities seen on CT and/or MR imaging in patients with COVID-19 and investigated possible associations between these findings and clinical parameters, including length of hospital stay, requirement for intubation, and development of acute kidney injury.MATERIALS AND METHODS: This was a retrospective study performed at a large academic hospital in the United States. A total of 641 patients presented to our institution between March 3, 2020, and May 6, 2020, for treatment of coronavirus disease 2019, of whom, 150 underwent CT and/or MR imaging of the brain. CT and/or MR imaging examinations were evaluated for the presence of hemorrhage, infarction, and leukoencephalopathy. The frequency of these findings was correlated with clinical variables, including body mass index, length of hospital stay, requirement for intubation, and development of acute kidney injury as documented in the electronic medical record.RESULTS: Of the 150 patients, 26 (17%) had abnormal CT and/or MR imaging findings, with hemorrhage in 11 of the patients (42%), infarction in 13 of the patients (50%), and leukoencephalopathy in 7 of the patients (27%). Significant associations were seen between abnormal CT/MR imaging findings and intensive care unit admission (P = .039), intubation (P = .004), and acute kidney injury (P = .030).CONCLUSIONS: A spectrum of acute neuroimaging abnormalities was seen in our cohort of patients with coronavirus disease 2019, including hemorrhage, infarction, and leukoencephalopathy. Significant associations between abnormal neuroimaging studies and markers of disease severity (intensive care unit admission, intubation, and acute kidney injury) suggest that patients with severe forms of coronavirus disease 2019 may have higher rates of neuroimaging abnormalities.COVID-19coronavirus disease 2019SARS-CoV-2Severe Acute Respiratory Syndrome coronavirus 2